An overview of bridge pier construction solutions, including the Indonesian approach - Marta Kiraga; Ananto Yusuf Wicaksono (Acta Scientiarum Polonorum. Architectura)
The paper provides an overview of the shape of the bridge piers, including the Indonesian approach. Universal principles of piers construction are provided, however the construction solutions placed in tropical climate conditions are determined by regional factors, such as considerations of resistance to earthquakes, tsunamis or frequent floods. The exemplary shapes of the pillars in the plan and the ways of their foundation are presented as a result of the analysis of English, Polish and Indonesian language literature. The economic role of bridge is emphasized in the context of Indonesian archipelago, where it constitute a central component of transportation system. The damage to the bridge is becoming particularly severe for the economy of the Indonesian archipelago. Therefore other climate invoke different engineerig problems. Structural solutions, which in a way respond to adverse climatic conditions are mainly using proper reinforcement in the case of piers, the drainage systems with a higher drainage capacity and metal components anti-corrosion treatment. Factors that should be considered in the design of the bridge pier shape, size, and configuration could be variously grouped and presented. From this study, following criteria can be distinguished: stability, location, seismic load, stream pressure, aesthetic, collision risk.